Children's reflections on privacy and the protection of their personal data: A child-centric approach to data protection information formats. (October 2021) - Milkaite, Ingrida; De Wolf, Ralf; Lievens, Eva; Leyn, Tom De; Martens, Marijn
Abstract: Ample research exists and focuses on teenagers' understanding of interpersonal privacy on social media. Less is known about younger children's understanding of privacy and data protection, especially in institutional and commercial data processing contexts. We have spoken to 83 children aged 9–12 years old in two public primary schools in the city of Ghent, Belgium. During the 16 workshops we conducted (which consisted of a focus group stage and a co-design exercise), we discussed children's everyday (online) activities and practices, their understanding of and views on interpersonal and institutional privacy, the privacy management techniques they use and the rights they have. The findings of our participatory research with young children provide insight into children's ideas and views about these issues. We report on a number of children's recommendations on how exactly information about privacy and data protection should be provided to them. The research has the potential to guide and inform both policymaking and the practical design of privacy and data policies by actors who process children's personal data.